2022
DOI: 10.3389/fpsyg.2021.823280
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Chinese EFL Students' Grit: The Impact of Teacher Stroke and Teacher-Student Rapport

Abstract: Due to the important role that students' grit plays in the effectiveness of their success in the educational system in which they are engaged, the current study scrutinized whether some factors regarding teachers such as their stroke and rapport can affect the learners' grit in one hand and on the other hand whether these factors can predict the learners' grit or not. To this end, a group of 316 Chinese university English as a Foreign Language (EFL) learners from more than 30 cities from nine provinces of Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…Fourth, students' grit and engagement can be enhanced through a wise juxtaposition with other positive constructs such as stroke, rapport, social support, and interpersonal communication skills (credibility, clarity, confirmation, and immediacy). This is well-substantiated by a recent study conducted by Yuan (2022) who examined the role of teacher stroke and rapport with students in developing Chinese EFL students' grit. Despite these insightful approaches, depending on teachers' experience and context, many more approaches can be proposed to enhance EFL students' grit and engagement that is obtainable by running complementary studies.…”
Section: Approaches To Enhance and Strengthen Students' Grit And Acad...mentioning
confidence: 73%
See 1 more Smart Citation
“…Fourth, students' grit and engagement can be enhanced through a wise juxtaposition with other positive constructs such as stroke, rapport, social support, and interpersonal communication skills (credibility, clarity, confirmation, and immediacy). This is well-substantiated by a recent study conducted by Yuan (2022) who examined the role of teacher stroke and rapport with students in developing Chinese EFL students' grit. Despite these insightful approaches, depending on teachers' experience and context, many more approaches can be proposed to enhance EFL students' grit and engagement that is obtainable by running complementary studies.…”
Section: Approaches To Enhance and Strengthen Students' Grit And Acad...mentioning
confidence: 73%
“…The construct of grit has been identified to cause academic success, interest, and efficiency in both general education and L2 education ( Keegan, 2017 ). Moreover, this positive psychological trait has been approved beneficial in psychology, medicine, and professional performance ( Sudina et al, 2021 ; Yuan, 2022 ). Owing to its prominent role in PP and SLA research, several correlational studies, in the past decade, have been carried out in different contexts showing that grit can predict students’ involvement and academic performance ( Hodge et al, 2018 ), wellbeing ( Jin and Kim, 2017 ), burnout ( Moen and Olsen, 2020 ), academic success ( Strayhorn, 2014 ; Reed and Jeremiah, 2017 ), resilience ( Shakir et al, 2020 ), achievement ( Steinmayr et al, 2018 ) and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, the personal, interpersonal, and situational sources of learner grit have remained elusive. Moreover, compared to other potential sources, interpersonal factors have gained far less attention ( Yuan, 2022 ). This inquiry sought to narrow the existing lacuna in the literature by inspecting the impact of two interpersonal factors, namely teacher respect and teacher support, on Chinese EFL learners’ grit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, the predictors of language learners’ grit have remained elusive. Put simply, factors leading language learners to become gritty have been rarely explored [e.g., Gyamfi and Lai (2020) , Yang (2021) , and Yuan (2022) ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding grit, Yuan (2022), in his study, revealed that teachers' communication behavior, such as teacher stroke and teacher-student rapport significantly affect learners' grit. He argued that teacher-student rapport and teacher stroke is related to students' grit.…”
Section: Literature Reviewmentioning
confidence: 99%